Statistics. A workbook for students - Awoyokun, A.A. (Ibadan : Fayi Publications, 1989)
This work book intends to show, through worked examples, and exercises some practical applications of statistical methods and to develop and stimulate the interest of students, educationists, business managers and administrators doubt the possibility of using statistics in their day-to-day management decisions.
osa 15/4/19
Loans
Keywords: Statistical mathematics; Nigeria